KARAKALPAK LITERATURE DURING THE PERIOD OF INDEPENDENCE - Orazymbetov Khuanishbai Kelimbetovich; Orazymbetova Marjangul Kelimbetovna (Galaxy International Interdisciplinary Research Journal, 2021)
The article deals with the Karakalpak literature of the period of Independence (1991-2019) as a whole. It reveals main features, some phenomena, achievements and shortcomings of the literature of that period. The works of some authors and popular books are generally analyzed.The article provides with plenty of factual materials, and they are compared with each other.The article reveals the main peculiarity of the progress of Karakalpak Literature in the last thirty years.